Azathioprine maintenance therapy in IBD:medium term outcomes from a nurse-delivered IBD monitoring service at a district general hospital. (13th March 2011) - Johnson, H E; McLaughlin, S D; Weaver, S A
Abstract : Introduction: Azathioprine is widely acknowledged as the benchmark therapy for maintenance of remission in IBD. Published long term outcome data from the district general hospital setting are limited. Methods: A prospective data base of IBD patients has been maintained at our unit since 2005. The authors reviewed the cases of all IBD patients commencing azathioprine treatment between June 2005 and December 2007 and followed up for at least 3 years. Thiopurine methyl transferase (TPMT) levels were checked on all patients. Azathioprine was prescribed at 2–2.5 mg/kg with dose reduction in patients with low TPMT. All patients complied with weekly blood monitoring for eight consecutive weeks. Clinical remission was defined as; a lack of symptoms in combination with Harvey Bradshaw Index (HBI) <5 for Crohn's disease (CD) or endoscopic remission for ulcerative colitis (UC). Abnormal liver function tests (LFTs) were defined as ALT 2× upper limit of normal (ULN). Results: 120 patients were identified (75 CD, 45 UC). 57 (47.1%) were male; mean age was 45 years (range 17–83). 12 of the 120 (10%) patients moved and were lost to follow-up leaving 108 under continuing follow-up. 47 (43.5%) were still taking azathioprine and 44 (93.6%) of these were in a clinical remission at the time of the study. Of the 44 patients in remission 8 patients have had surgery but remain on azathioprine. Of the 61 patients who stopped azathioprine, median time to cessation 5 weeks (range 0.14–208). Reasons for stopping azathioprine were; Pancreatitis; 2 (3.3%), Low total white blood cell count; 4 (6.6%), Surgery; 9 (14.8%), Abnormal liver function tests (LFTs); 14 (23%), Side effects including myalgia, flu symptoms, rashes, nausea and vomiting and patient choice; 32 (26.7%). Treatment for the 61 patients stopping azathioprine were as follows: Mercaptopurine; 12 (19.7%), methotrexate; 4 (6.6%), Biologics; 6 (9.9%), 5-ASA; 28 (44.7%), Colectomy; 2 (3.3%), no treatment; 9 (14.8%). Conclusion: These results demonstrate that in our unit more than half of patients failed to continue azathioprine in the medium term. This is higher than reported in tertiary centres. In those patients who continued azathioprine more than 90% were in a clinical remission at last follow-up. The majority of patients where treatment was stopped was because of side effects or abnormal LFTs. A recently published study has demonstrated that allopurinol in combination with low-dose azathioprine can bypass many adverse drug reactions and enable patients to continue azathioprine. The authors now routinely test 6-Thioguaine nucleotide levels and use allopurinol co-therapy in such patients. The authors aim to perform a further study to establish whether this treatment strategy will allow more of our patients to continue azathioprine.